MENGATASI TANTANGAN LITERASI Al-QUR'AN: METODE EFEKTIF DALAM PEMBELAJARAAN BACA TULIS - Nur, Fakhriyah; Nuradillah, Ainun; Jumardi; Munir, Syahrul; Rahmah, Nur; Muhammad, Fadel; Mulianah, Sri (Prodi Pendidikan Agama Islam, 2025)
This research aims to examine methods for learning to read and write the Al-Qur'an by combining others. This research is research with a qualitative approach to the case study type. This research was conducted at an Islamic educational institution with the principal, tutors and students as subjects. Data was taken by means of interviews, observation and documentation which in turn provided an overview of the practice of this method. The thematic analysis method was chosen to answer questions related to method effectiveness, use of technology and understanding of the values ​​of the Koran. The results of this research show that this hybrid method really helps improve students' reading skills and language guidance. Students' reading skills, recitation and self-esteem regarding completing learning tasks experienced positive changes. The results recommend deeper research regarding alternative and hybrid models of Al-Qur'an literacy in educational institutions. At least so, this kind of approach increases students' attention to the learning process by using technology in the right portion, strengthening theories that have been proven conventionally. This research is at an important gap in teaching the Al-Qur'an with a considered, appropriate and more international approach in the contemporary context and the media..